Result Evaluation of Dynamic Topology Control Using Quality Estimation Factors for Mobile Ad-Hoc Network (International Journal of Engineering and Computer Science, 2015)
Mobile ad-hoc network support dynamic topology handling due to their variable nature of communicating nodes. Here themotion of nodes is random in a specified range of the network. As the mobile nodes containlight weighted protocols forsupporting transmissions, it requires some more controls over the topological aspect. The traditional topology control mechanismcan be categorised according to their use like mobility sensitive, energy awareness, QoS based etc. An efficient protocol is thatwhich dynamically handles all this issues effectively with better use of bandwidth.Problem:The aim is to investigate the shortcomings of current solutions with respect to the dynamic topology handling issuesthrough QoS based transmissions, and bring forth new solutions to improve the performance of the network as a whole or for theindividual nodes. With respect to the issue of mobility, and traffic distribution, the work focuses to investigate the factors thataffect the rerouting time in proactive routing protocols. That is, the time duration needed to reroute and restore a brokencommunication path due to node mobility.